Hard and soft-tissue evaluation of bar-clip, ball-socket, and kerator attachments in mandibular implant overdenture treatment: An in vivo study - Varshney, Nitish (J Indian Prosthodont Soc, 2019)
AIM: The aim of this in vivo study was to evaluate and compare the soft and hard tissue changes in implant supported mandibular overdenture with three different attachment system. SETTINGS AND DESIGN: In vivo – observation study. MATERIALS AND METHODS: After evaluation of prosthetic space, fifteen edentulous subjects received two implants in the inter-foramina region of the mandible and were divided into 3 groups with 5 subjects each, delayed loading protocol was followed in all the patients. The crestal bone loss, modified sulcular bleeding index, plaque index values were evaluate with the attachments at baseline and after 6 months was measured in a standardised way. STATISTICAL ANALYSIS USED: Oneway ANOVA test and post hoc Bonferroni multiple test. RESULTS: At the end of six months modified sulcular bleeding index and plaque index values was higher in Group 2 (bar and clip attachment) as compared to Group 1 (ball and socket attachment) and Group 3 (Kerator attachment) and crestal bone loss was equal in groups 1, 2 and 3. Analysis of variance with repeated measures showed significant differences in modified sulcular bleeding index and plaque index among the three attachment types. CONCLUSION: (1) Group 2 (bar-and-clip attachment) exhibited higher Modified Sulcular Bleeding Index and Plaque Index values than Group 1 (ball-and-socket attachment) and Group 3 (kerator attachment). (2) Crestal bone loss was equal in Group 1 (ball-and-socket attachment), Group 2 (bar-and-clip attachment), and Group 3 (kerator attachment).